Immediate Online Public Access to Theses as a Graduation Requirement: Current State and Reflections - One-Soon Her; Pei-Hsuan Ho; Ying-Chen Lin; Wen-Yau Cathy Lin (Journal of Library and Information Studies)
In Taiwan, a thesis remains a necessary condition for universities to award master’s and doctoral degrees in most fields. It is a mutually beneficial outcome of collaboration between the university and the student. Its social value and credibility must be built upon the foundation of its substance that matches its reputation. Based on the universal value of academic dissemination and the added benefit of preventing plagiarism, the disclosure of theses for public scrutiny should be necessary for degree theses. In this study, we first examine the current state of requirements for public release of theses, based on relevant national laws and university regulations. We then present arguments from academic and legal perspectives, asserting that in the modern era of internet access, it is reasonable and appropriate for universities to make online access to degree theses a graduation requirement. Using open-access journal articles as an analogy, we suggest that universities explicitly incorporate this graduation requirement into their academic regulations through due process to avoid any legal challenges. Finally, we clarify the supporting role of electronic plagiarism detection systems, emphasizing that the real underpinnings of academic research are academic ethics education and the professionalism and morals of professors and students. (Article content in Chinese with English extended abstract)